Assessing Mon Ceunong Waterfall as an Emerging Nature-Based Tourism Destination: A 4A Approach - Eka octavian Pranata; Arinal Rahmati; Ika Indah Smaradhani; Nur khotimah; Karinta fakhira (Program Studi Pariwisata Syariah - UIN Sjech M. Djamil Djambek Bukttinggi, 2026)
This article examines the development potential of Mon Ceunong Waterfall, a nature-based tourism destination located in Indrapuri, Aceh Besar, Indonesia. The study applies a descriptive qualitative approach using a literature study method, drawing on data from online publications, tourism portals, and media reports. The analysis is structured using the 4A tourism framework: attraction, accessibility, amenities, and ancillary services. The findings indicate that Mon Ceunong Waterfall has strong natural attractiveness and experiential value, yet faces significant challenges in accessibility, infrastructure, and institutional support. The study highlights the importance of integrated destination management and sustainable tourism strategies to enhance its competitiveness. This research contributes to the discourse on emerging rural tourism destinations, particularly in underdeveloped regions of Indonesia.